IMPLEMENTASI PENGELOLAAN DANA DESA BIDANG PEMBERDAYAAN MASYARAKAT DITENGAH GEJOLAK TURBULENSI KEUANGAN DESA (Studi Kasus Desa Buntongi Kecamatan Ampana Kota Kabupaten Tojo Una Una) - Wisra W; Siti Aminah H. Karim; Rosida P Adam; Suardi S; Nurfia N; Sulvia Verawaty (AGRIBUSINESS JOURNAL, 2019)
The purpose of this study is to describe the management of village funds in community empowerment and find out the problems that exist so that it allows management of village funds is not going well. This study uses a descriptive qualitative method with the Phenomenology-Hermeneutics approach which is used to find the meaning and nature of the informant's experience. Buntongi Village, Ampana District, Tojo Una Una Regency is the object of this research activity with informants from the Village Head, Secretary, Village Treasurer, Head of Government, BPD and the community. The results showed that the management of village funds was recorded vertically to the sub-district head, so we conclude that the management of village funds especially the absorption of spending in the field of Community Empowerment has not been carried out properly.